Perancangan User Interface Marketplace UKM Batik Menggunakan Metode User Centered Design (UCD) - Santoso, R.P Mohammad Bagus; Sagirani, Tri; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
The condition of batik sales in Pamekasan Regency decreased. This is because the batik craftsmen still use traditional marketing methods and have a small scale of consumer. The results of interviews with several batik craftsmen in Pamekasan District revealed that they needed solutions to increase sales and expand their market. The solutions for this problem is using a marketplace to sell their product. Marketplace as an online media can help batik craftsmen to expand their marketi to a bigger scale. The user interface in the marketplace is one of the determining factors whether the user will continue to use the marketplace or not. The user interface of the marketplace uses the User Centered Design (UCD) method that produces a design mockup. The resulting mockup has been tested using the usability testing method by distributing questionnaires to 50 respondents. There are 5 variables used, namely learnability, efficiency, memorability, errors and satisfaction. The results of the tests show that the mockup of the user interface design shows learnability accuracy is 84%, efficiency accuracy is 86.2%, memorability accuracy is 88%, accuracy of errors is 82% and 87.5% for satisfaction. Keywords: batik, user interface, user centered design